2021
DOI: 10.1242/dev.199409
|View full text |Cite
|
Sign up to set email alerts
|

The multiple facets of Cajal-Retzius neurons

Abstract: Cajal-Retzius neurons (CRs) are among the first-born neurons in the developing cortex of reptiles, birds and mammals, including humans. The peculiarity of CRs lies in the fact they are initially embedded into the immature neuronal network before being almost completely eliminated by cell death at the end of cortical development. CRs are best known for controlling the migration of glutamatergic neurons and the formation of cortical layers through the secretion of the glycoprotein reelin. However, they have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 160 publications
(219 reference statements)
0
47
0
Order By: Relevance
“…MGE/PoA-derived neurons were identified based on their expression of Lhx6 (LIM homeobox 6) ( Alifragis et al, 2004 ), while newborn cholinergic neurons expressed Gbx2 (gastrulation brain homeobox 2) ( Asbreuk et al, 2002 ; Chen et al, 2010 ); we also identified Dner (delta/notch-like EGF repeat containing) as a general marker for septal neurons ( Figure 1G and H ). We identified additional distinct newborn neuronal populations, including presumptive pallium-derived neurons expressing Tbr1 (T-box brain transcription factor 1) ( Bulfone et al, 1995 ), septum-derived Cajal-Retzius cells ( Bielle et al, 2005 ) expressing Trp73 (transformation-related protein 73) ( Causeret et al, 2021 ; Meyer et al, 2004 ), and presumptive LGE-derived neurons expressing Isl1 (ISL LIM homeobox 1) ( Stenman et al, 2003 ; Toresson et al, 2000 ; Figure 1—figure supplement 2D and E ). The expression of these genes was restricted to the mantle zones of the MGE and the developing septum, further confirming that they are markers of postmitotic neurons, rather than progenitors ( Figure 1G and H , Figure 1—figure supplement 1C , Figure 1—figure supplement 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…MGE/PoA-derived neurons were identified based on their expression of Lhx6 (LIM homeobox 6) ( Alifragis et al, 2004 ), while newborn cholinergic neurons expressed Gbx2 (gastrulation brain homeobox 2) ( Asbreuk et al, 2002 ; Chen et al, 2010 ); we also identified Dner (delta/notch-like EGF repeat containing) as a general marker for septal neurons ( Figure 1G and H ). We identified additional distinct newborn neuronal populations, including presumptive pallium-derived neurons expressing Tbr1 (T-box brain transcription factor 1) ( Bulfone et al, 1995 ), septum-derived Cajal-Retzius cells ( Bielle et al, 2005 ) expressing Trp73 (transformation-related protein 73) ( Causeret et al, 2021 ; Meyer et al, 2004 ), and presumptive LGE-derived neurons expressing Isl1 (ISL LIM homeobox 1) ( Stenman et al, 2003 ; Toresson et al, 2000 ; Figure 1—figure supplement 2D and E ). The expression of these genes was restricted to the mantle zones of the MGE and the developing septum, further confirming that they are markers of postmitotic neurons, rather than progenitors ( Figure 1G and H , Figure 1—figure supplement 1C , Figure 1—figure supplement 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Potential pathways of HAR1A affecting cortical development through CRs HAR1A is speci cally expressed in CRs, which existed in the developing human neocortex during gestational weeks 7-19 (18). CRs is crucial in the speci cation and migration of cortical neuron, suggesting that HAR1A plays an impotent role in neurogenesis (19). The results of GO analysis of DEGs showed that cerebral cortex development had the lowest p-value in all GO items related to brain development.…”
Section: Discussionmentioning
confidence: 96%
“…Our study, together with previous work, put forward a recursive model of cortical development involving sequences. More specifically, CRc exert multiple functions at specific time points of their “short” lives: (1) they regulate neocortical lamination, interneuron distribution, and axonal navigation in the embryo ( Causeret et al., 2021 ; Genescu and Garel, 2021 ; Gesuita and Karayannis, 2021 ; Kirischuk et al., 2014 ); (2) they are redistributed in an activity-dependent manner and their embryonic distribution relies on spontaneous activity of the thalamus; (3) CRc coordinately act upon key aspects of L1 development during postnatal development with long-term functional consequences; (4) subsets of CRc are dismissed by an activity-dependent mechanism that remains to be characterized ( Riva et al., 2019 ). All of these steps ensure the proper wiring of cortical circuits.…”
Section: Discussionmentioning
confidence: 99%
“…CRc are glutamatergic early-born neurons, best known for their roles in lamination and the production of the secreted glycoprotein Reelin ( D’Arcangelo et al., 1995 ; Kirischuk et al., 2014 ; Tissir et al., 2009 ). CRc are produced by focal sources, migrate tangentially, and tile the neocortical surface, in part via contact repulsion ( Barber et al., 2015 ; Barber and Pierani, 2016 ; Bielle et al., 2005 ; Causeret et al., 2021 ; Griveau et al., 2010 ; Ruiz-Reig et al., 2017 ; Villar-Cerviño et al., 2013 ; Yoshida et al., 2006 ). CRc undergo postnatal apoptosis in the neocortex, until their almost complete elimination by postnatal day (P) 25 ( Blanquie et al., 2017 ; Causeret et al., 2018 ; Ledonne et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%